Costo de reprocesamiento de productos dañados y material de desecho, empresa C.A. ECUATORIANA DE CERAMICA de la ciudad de Riobamba, período 2021. - Aguirre Enríquez, Elizabeth Estefanía (2023)
The present investigative work was developed with the purpose of analyzing the reprocessing treatment for damaged products and waste materials raised in the following research project, it is of great relevance within the company since its objective is to analyze the investment costs to recover such losses caused during the production process. This project bases its investigation on the costs reflected in the financial statements of the company C.A. ECUATORIANA DE CERÁMICA period 2021 through procedures and quantitative analysis supported by documentary and physical verification, which allow at the end of this document to issue conclusions and recommendations with reasonable criteria.